USING VIRTUAL LEARNING ENVIRONMENT ON REALISTIC MATHEMATICS EDUCATION TO ENHANCE SEVENTH GRADERS’ MATHEMATICAL MODELING ABILITY - Denny Haris (SCHOOL EDUCATION JOURNAL PGSD FIP UNIMED, 2022)
Many research studied that realistic mathematics education (RME) can be an alternative solution to students’ difficulties in learning mathematics. Various forms of technology additionally are further employed to support students' mathematical achievements. However, research on the implementation of virtual learning environments (VLE) with the RME approach is still lacking. The main goals of this research were to create an instructional process of virtual learning environments on realistic mathematics education to improve seventh graders' mathematical modeling abilities and to examine the effect of designs on mathematical modeling ability. Theory of realistic mathematics education and virtual learning environment literature were integrated. The design model developed was verified by experts to be tested. The pre-test / post-test test method was carried out to see the effectiveness of the design. The sixty-seventh graders from a secondary school in North Sumatera were selected as samples. The instructional process developed consists of four stages, namely (1) purposing contextual problems, (2) defining situations from contextual problems, (3) solving problems individually or in groups, and (4) reviewing and comparing solutions. The developed virtual learning environment consists of 5 components, namely (1) users management, (2) content and activities management, (3) resources management, (4) visualization and communication management, and (5) evaluation and assessment management. The mathematical modeling ability concerning experimental group students is significantly higher after being taught through a realistic mathematics education instructional process via a virtual learning environment. Comparison of the experimental group with the control group also showed the same results.